An Assessment of the Ability of the U.S. Department of Defense and the Services to Measure and Track Language and Culture Training and Capabilities Among General Purpose Forces - DeCamp, Jennifer (RAND Corporation, 2012)
This report addresses questions concerning the U.S. Department of Defense's ability to measure and track the language, regional expertise, and culture (LREC) training and capabilities of general purpose forces. The authors used interviews with LREC practitioners and policymakers, a policy review, an academic literature review, and an analysis of survey data to address the research questions.